Materializing narratives: The story behind the story. (November 2021) - Canagarajah, Suresh
Abstract: Though narrative studies have moved beyond the analysis of narratives as a finished product to their social shaping under the label narrative analysis, material resources add another level of complexity to the analysis of narratives. The sociomaterial orientation theorizes why we must move beyond treating people as the only agents or protagonists of their narratives, and consider the engagement of diverse spatial and material resources in the shaping of their stories and their identities. In such an analysis, material resources which are traditionally relegated to context and separated from the text must be integrated in textual and narrative analysis. Michael Silverstein's notions of recontextualization (i.e., "the process of how discourse points to (indexes) the context which seems to frame it") and entextualization (i.e., "the process of coming to textual formedness" −2019: 56) from sociolinguistics have helped scholars analyze the ongoing interactions between the text and context. The sociolinguistic notion of frames helps to determine which resources are critical for contexualizing the ongoing entextualization of the narrative.